Proceso de atención de enfermería en paciente de 38 años con diabetes mellitus tipo 2. - Velásquez Alcívar, Gabriela Yustin (2020)
Diabetes is a pathology that seriously affects Ecuador, being the third cause of death in the country, an indicator that should promote the population to have a better food quality and avoid suffering from this disease. The patient to be treated is a 38-year-old woman with 37.6 weeks of gestation who suffers from type II diabetes mellitus with a progression of 5 years.According to nutritional assessment, the patient reports being overweight according to the BMI indicator (Body Mass Index), in Regarding relevant biochemical examinations, their glycosylated hemoglobin values are within normal parameters, which reveals that the patient has controlled diabetes, however, he presented ulcerative lesions in the lower limbs, for which a nursing intervention was applied for his Recovery.